Dietary exposures, epigenetics and pubertal tempo. Issue 1 (7th March 2019) - Wu, Yue; Sánchez, Brisa N; Goodrich, Jaclyn M; Dolinoy, Dana C; Cantoral, Alejandra; Mercado-Garcia, Adriana; Ruiz-Narváez, Edward A; Téllez-Rojo, Martha M; Peterson, Karen E
Abstract: Gene expression changes mediated by DNA methylation may play a role in pubertal tempo regulation, and availability of methyl donor nutrients affects these pathways. We examined first trimester maternal and adolescent diet patterns that may be associated with DNA methylation at long interspersed nucleotide (LINE-1) repetitive elements in adolescence using least absolute shrinkage and selection operator (LASSO) and calculated an 'Epigenetics-Associated Diet Score' (EADS) for each pattern; then tested the associations of these scores with pubertal tempo among adolescent boys and girls. The analytic sample included 118 boys and 132 girls aged 10–18 years. DNA methylation at LINE-1 repetitive elements was quantified. Typical maternal and adolescent nutrient intakes were estimated using food frequency questionnaires. Interval-censored time to event and ordinal regression models were used to examine associations EADS scores with pubertal tempo using physician-assessed Tanner stages and self-reported menarche, respectively, adjusted for confounders. We observed associations between maternal EADS and pubertal onset, but not pubertal progression. Each standard deviation (SD) greater maternal EADS was associated with 52% higher odds of having later onset of menarche in both cross-sectional and prospective analysis ( P = 0.031 and 0.028, respectively). In contrast, we observed associations between adolescent EADS and pubertal progression, but not pubertal onset. Among boys, for each SD higher adolescent EADS, there was 13% increase in odds of slower genital progression ( P = 0.050), as well as 26 and 27% increase in odds of slower left and right testicular development, respectively ( P = 0.001). Epigenetic-associated diet influences pubertal tempo in a sex- and timing-specific manner.